The influence of an accompanying substance on the adsorption of herbicides on activated carbon in a multi-component system - Magdalena Blachnio; Malgorzata Zienkiewicz-Strzalka; Anna Derylo-Marczewska (Desalination and Water Treatment)
The aim of this study was to determine the influence of selected co-adsorbates on the adsorption process of herbicides on activated carbons. 4-Chlorophenoxyacetic acid (4-CPA) and 3-chlorophenoxypropionic acid (3-CPP) were tested as herbicidal active substances. The accompanying substances included 2-nitrophenol (2-NP), 4-nitrophenol (4-NP), 4-nitroaniline (4-NA) and crystal violet (CV). Activated carbon materials were fully characterized by nitrogen adsorption/desorption isotherms, potentiometric titration, X-ray photoelectron spectroscopy, and transmission electron microscopy. Adsorption processes from aqueous solutions were investigated using the static method. The Generalized Langmuir equation (GL) was applied to analyze the adsorption isotherms. Kinetic measurements were also carried out to better understand the mutual influence of herbicides with co-adsorbates. The influence of the properties of co-adsorbates and adsorbents on the efficiency of herbicide removal from the water phase was discussed.